Report on proposed new interior design of Malaysian Red Devils Restaurant at Unit 7, USJ 10/1 Taipan Triangle Subang Jaya, Selangor Darul Ehsan / Mohd Salleh Ismail - Ismail, Mohd Salleh (Faculty of Architecture, Planning and Surveying, 2010)
The final project for the student of Diploma in Interior Design is a manifestation towards the student’s knowledge about the whole aspect on interior design that had been learnt from basic to the final presentation on the proposed design. The project that had been chosen for the final project is to propose a new interior design for the interior of Malaysian Red Devils Restaurant at unit 7, Usj 10/1 Taipan Triangle Subang Jaya, Selangor Darul Ehsan. This proposed fan club restaurant is to attract costumer, mostly the Mancheter United fans to come and gather at the fan club restaurant always The target custumer is all the Manchester United fans. Concept and image that had been chosen not only must be suitable with the clients as both of it would reflect the client itself, but at the same time it would give a positive impact to the restaurant.